Standardized Nutrition Care Process for Critically Ill Patients with Traumatic Brain Injury, Pulmonary Contusion, and Alcohol Intoxication - Diyan Yunanto Setyaji; Isti Suryani; Nugraheni Tri Lestari; Slamet Iskandar; Meike Mayasari (Journal of Global Nutrition, 2025)
Disturbed intake factors, hypermetabolism and hypercatabolism in critical patients cause increased energy needs. Critical patients are very susceptible to nutritional deficiencies resulting in decreased immune systems, poor wound healing, and organ failure that prolongs hospitalization and increases mortality. In these circumstances, nutrition becomes an important part of clinical medical therapy. This study was conducted to implement nutritional services and standardized nutritional care processes in patients with a medical diagnosis of Decreased Consciousness e.c. Severe Head Injury e.c. Traumatic Intracerebral Haemorrhage (TICH), Traumatic Subarachnoid Haemorrhage (TSAH), Intraventricular Haemorrhage (IVH), Pulmonary Contusion, Right Antebrachial Trauma, Close Fracture Ulna 1/3 Distal Right, Alcohol Intoxication, Brainstem Contusion in the Gatotkaca Ward 4 MICU Dr. Sardjito General Hospital. This study uses a descriptive qualitative research design with a case study design. This study used primary and secondary data with data presentation in narrative, tabular, and graphical form. Based on NRS 2002 screening, the patient was at risk of malnutrition. The food intake graph for six days with a high energy and protein diet in the form of enteral per NGT or parenteral diet showed fluctuations in intake from 8.30% on the first day to 33.78% on the sixth day. Acceptance of the NGT diet decreased since the third day as indicated by low absorption and gastric residue. The results of the blood gas analysis showed that the patient had respiratory acidosis. It can be concluded that the standardized nutritional care process and collaboration between health professionals that are carried out optimally and intensively cannot always provide a good prognosis in cases of severe head injury with various complications such as alcohol intoxication, pulmonary contusion, and brainstem contusion.